"A Tribe Apart": Sexuality and Cancer in Adolescence. (July 2017) - Moules, Nancy J.; Estefan, Andrew; Laing, Catherine M.; Schulte, Fiona; Guilcher, Gregory M. T.; Field, James C.; Strother, Douglas
This qualitative study employed hermeneutic phenomenology and narrative inquiry to examine the topic of sexuality and adolescents with cancer from the perspectives of survivors who had experienced cancer as adolescents. This investigation examined the potentially sensitive, disquieting, and often taboo issue of sexuality in the interest of optimizing wellness in young people, and, ultimately, in the health of adults. Understanding the adolescent body as a sensitive, sexual, and developing self can enrich our understanding of adolescent cancer and promote best health care and practices, examining ways that we might mitigate the long-term effects of arrested or delayed development of sexual identity. In this article, we discuss phase 1 of the study, which used hermeneutics as the method of inquiry. Findings included a general experience of adolescents having a sense of "losing themselves" while at the same time finding themselves in a new light. Other findings include the connection between sexuality, self, and identity; the unique "tribe" of adolescents with cancer; the necessity for sexuality to take a backseat to cancer; the changing mirror images from self and others; sexuality and fertility; and, ultimately, that sexuality is a relational experience.